United Nations E-Government Survey 2018 - United Nations (United Nations, 2018)
Governments have the critical responsibility to pursue policies and measures to build resilience and assist those most affected by shocks in achieving the Sustainable Development Goals (SDGs). They must find ways to anticipate disasters and shocks and lower their impact. Digital technologies are increasingly being used by governments to improve the response to disasters and other shocks to improve the resilience of communities. In the information society, it is important to move onwards to an approach where the concerns of building resilience, sustainable development and leaving no one behind are embedded in e-government development.